Category predication work, discursive leadership and strategic sensemaking. (March 2015) - Whittle, Andrea; Housley, William; Gilchrist, Alan; Mueller, Frank; Lenney, Peter
Categorization is known to play an important role in organizations because categories 'frame' situations in particular ways, informing managerial sensemaking and enabling managerial intervention. In this article, we advance existing work by examining the role of categorization practices in discursive leadership during periods of strategic change. Drawing on data from an ethnographic action research study of a strategic change initiative in a multi-national corporation, we use membership categorization analysis to develop a framework for studying 'category predicates' − defined as the stock of organizational knowledge and associated reasoning procedures concerning the kinds of activities, attributes, rights, responsibilities, expectations, and so on, that are 'tied' or 'bound' to organizational categories. Our analysis shows that discursive leadership enabled a radical shift in sensemaking about organizational structure categories through a process of 'frame-breaking' and 're-framing'. In so doing, the leader co-constructed a 'definition of the situation' that built a compelling vision and concrete plan for strategic change. We go on to trace the organizational consequences and material outcomes of this shift in sensemaking for the company in question. We conclude by arguing that 'category predication work' comprises a key leadership competence and plays an important role in organizational and strategic change processes.